Argon and nitrogen beams influencing membrane permeate fluxes and microbial growth - P. Wanichapichart (2018)
Porous cellulose and dense chitosan membranes were bombarded with argon and nitrogen-ion beams using two energy levels, 30 and 120 keV, of the same fluency of 5×1014ions/cm2for a comparison study. The results revealed that both beam types reduced the hydraulic permeability of the membranes. Using a NaCl solution of 4000 ppm concentration as feed, the ability to reject salt of dense chitosan membrane was reduced only if it was pretreated with 120 keV nitrogen-ion beams. A Fourier Transform Infrared Spectroscopy study showed that molecular weight of chitosan was possibly decreased after the bombardment with 120 keV beams. The analysis of the cellulose membranes revealed that a dense structure was created without affecting the OH functional groups. This study found that only chitosan membranes possessed an anti-fungi property if being implanted with positive charges of nitrogen or argon ions of 120 keV. © 2009 Elsevier Ltd. All rights reserved.